2015
DOI: 10.17507/tpls.0504.14
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Iranian EFL Learners' Multiple Intelligences and Their Learning Styles

Abstract: Abstract-The current work reports investigation of the relationship between Iranian EFL learners' multiple intelligence (MI) profiles and their learning styles (LSs). The study also attempts to find out the most and the least dominant learning styles among the participants. The study further examines whether there is any significant difference between genders in using the different types of learning styles. To this end, two questionnaires, a 90-item multiple intelligences questionnaire and a 24-item learning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This result was parallel with Panahandeh et al (2015)'s study. In the study, some positive relationship between learning styles and intelligences in terms of gender and intelligences types, especially, were found.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result was parallel with Panahandeh et al (2015)'s study. In the study, some positive relationship between learning styles and intelligences in terms of gender and intelligences types, especially, were found.…”
Section: Discussionsupporting
confidence: 87%
“…A statistically significant relationship between learning styles and multiple intelligences was also determined. Similarly, in the Iranian context, Panahandeh et al (2015) conducted a study to identify the relationship between EFL learners' multiple intelligences and their learning styles. They also focused on the most and the least dominant learning styles and investigated the difference between genders.…”
mentioning
confidence: 99%
“…In studies examining the relationship between high school students' multiple intelligences and learning styles, there is a positive relationship between learning style and multiple intelligence domains (Baleghizadeh & Shayeghi, 2014;Snyder, 1999;Alrabah, Wu & Alotaibi, 2018). In studies examining the relationship between intelligence types and learning styles of university students, it was found that there are significant differences between the intelligence domain and learning style (Tekiner, 2005;Seifoori & Zarei, 2011;Panahandeh, Khoshkhoonejad, Mansourzadeh, & Heidari, 2015;Aygül & Koç, 2016;Şener and Çokçalıkan 2018). This research and the results of similar studies in the literature show that multiple intelligences significantly affect students' learning styles and students tend to prefer learning styles that are compatible with their intelligence preferences.…”
Section: Findings and Discussion Of The Third Research Aimmentioning
confidence: 99%
“…Baleghizadeh & Shayeghi (2014) analyzed the relationship between Iranian students' multiple intelligence types and learning styles in different age groups and found a statistically significant difference. Panahandeh, Khoshkhoonejad, Mansourzadeh & Heidari (2015) examined the relationship between university students' multiple intelligence and learning styles and determined significant differences between learning styles and intelligence types. Aygül & Koç (2016) found a statistically significant difference between vocational high school students' multiple intelligence and their teaching styles.…”
Section: Introductionmentioning
confidence: 99%